Current concepts in ameloblastoma-targeted therapies in B-raf proto-oncogene serine/threonine kinase V600E mutation: Systematic review - González-González, Rogelio (World J Clin Oncol, 2020)
BACKGROUND: Ameloblastomas are common benign epithelial odontogenic neoplasms that present an aggressive and unpredictable behavior that may modify treatment strategies. Different signaling pathways that participate in the progression of these tumors have been identified. B-raf proto-oncogene serine/threonine kinase (BRAF) is a protein involved in the behavior of ameloblastomas, and it is related to many cell mechanisms. BRAF gene mutations have been identified in ameloblastomas, of which the BRAF V600E (valine substituted by glutamic acid at amino acid 600) mutation has been the most common and can be present concomitantly with other mutations that may be involved in its behavior. Targeted therapies have been used as an alternative in the case of resistance or contraindications to conventional treatments. AIM: To document the presence of BRAF V600E and additional mutations, their behavior, and targeted therapies in these tumors. METHODS: An electronic literature search was conducted according to PRISMA guidelines in PubMed/MEDLINE, Cochrane, EMBASE, and SpringerLink using the terms “ameloblastomas”, “BRAF V600E”, “additional mutations”, and “targeted therapies”. Ameloblastomas were classified according to WHO guidelines. Inclusion criteria were articles in English, published not more than 10 years ago, and studies with laboratory works related to BRAF V600E. Articles were evaluated by two independent reviewers and retrieved for full-text evaluation. The EBLIP Critical Appraisal Checklist was used to evaluate the quality of the eligible studies. Descriptive statistical analysis was performed. RESULTS: Two independent reviewers, with a substantial concordance indicated by a kappa coefficient of k = 0.76, evaluated a total of 19 articles that were included in this study. The analysis registered 521 conventional ameloblastomas (AM), 81 unicystic ameloblastomas (UA), 13 ameloblastic carcinomas (AC), three metastatic ameloblastomas (MA), and six peripheral ameloblastomas (PA), of which the histopathological type, anatomic location, laboratory tests, expression of BRAF mutation, and additional mutations were registered. The BRAF V600E mutation was found in 297 AM (57%), 63 UA (77.7%), 3 AC (23%), 1 MA (50%), and 5 PA (83.3%). Follicular type predominated with a total of 116 cases (40%), followed by plexiform type with 63 cases (22.1%). Furthermore, both types presented additional mutations, in which alterations in JAK3 P132T, SMARCB1, PIK3CA, CTNNB1, SMO, and BRAF G606E genes were found. Four case reports were found with targeted therapy to BRAF V600E. CONCLUSION: The identification of BRAF V600E and additional mutations as an aid in targeted therapies has been a breakthrough in alternative treatments of ameloblastomas where surgical treatments are contraindicated.